2013
DOI: 10.1891/0730-0832.32.4.246
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Neonatal Ventilation: Strategies for Decision Making in the NICU

Abstract: Neonatal ventilation is an integral component of care delivered in the neonatal unit. The aim of any ventilation strategy is to support the neonate's respiratory system during compromise while limiting any long-term damage to the lungs. Understanding the principles behind neonatal ventilation is essential so that health professionals caring for sick neonates and families have the necessary knowledge to understand best practice. Given the range of existing ventilation modes and parameters available, these requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Guidelines for the use of pressure-limited ventilation in neonates are limited [4,14]. According to the Handbook for Neonatal Intensive Care, the recommendations for starting pressures for beginning ventilator support are PIPs of 16-20 cmH 2 O [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines for the use of pressure-limited ventilation in neonates are limited [4,14]. According to the Handbook for Neonatal Intensive Care, the recommendations for starting pressures for beginning ventilator support are PIPs of 16-20 cmH 2 O [15].…”
Section: Discussionmentioning
confidence: 99%
“…Neonates < 32 weeks gestation on continuous positive airway pressure were found to have an average VT of 4.4 ml/kg with a wide range of 2.6-7.2 ml/kg [27]. Typical VT ranges to initiate VTV range from 4 to 7 ml/kg [3,4,14] but in a survey from European neonatal intensive care units, 18% used VT > 7 ml/ kg [4]. Although some authors have suggested that VT > 8 ml/ kg can cause volutrauma [28,29], it is important to note that any positive pressure ventilation can cause cyclic trauma up to 86,000 times/day [30].…”
Section: Discussionmentioning
confidence: 99%
“…22,30 The knowledge base ("rules") within an explicit mechanical ventilation CDSS needs to be extensive and detailed to capture the rich nuances of critically ill children. 31 A major concern is obtaining agreement on what medical knowledge to implement within the CDSS. 20 Published work on respiratory physiology, observational studies of ventilator management strategies and current practices, clinical trials, consensus conference findings, and expert clinician knowledge need to be synthesized to define decision points.…”
Section: Cdss Knowledge Developmentmentioning
confidence: 99%